Suicide risk assessment method and system based on artificial intelligence, and computer storage medium - LIU PANSHI; ZHANG HUI; YANG GUOQIANG (2025)
The invention relates to a suicide risk assessment method and system based on artificial intelligence, and a computer storage medium. The method comprises the following steps: acquiring brain MRI data information of a target person; loading the brain MRI data information into a trained neural network extraction model to extract a coding feature vector of the brain MRI data information corresponding to the target person; and inputting the brain activity feature vector into a risk factor assessment model to obtain a risk assessment result of the target person. On the other hand, space and time modes of brain activities are accurately captured through an improved algorithm and a data processing flow, on the other hand, dependence on subjective reports of subjects is reduced, and objectivity and accuracy of evaluation are improved by directly extracting information from nerve image data. Data inaccuracy of a traditional questionnaire caused by a hidden problem of a subject can be effectively avoided, and a more r